Wand of Elder, never prosper : Imagination and Reality in Harry Potter and the Deathly Hallows - Santos, João (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2017)
My purpose with this paper will be to offer a view on magic in Harry Potter and the Deathly Hallows by analyzing one of the novel‟s hallows, the Elder Wand. Through an analysis of this wand, which is said to be the most powerful wand ever made in the entire Harry Potter universe, I wish to discuss the many possibilities magic can offer in the world of witches and wizards, but also the limits that exist in the realm of magic. I will argue that, despite its many properties and its enticing realm, magic is not all-powerful, but rather something illusory that simply inspires one‟s imagination. I will further propound that, although it is the main instrument of survival in the Harry Potter universe, even the protagonist‟s actions evince that a balance between imagination and reality must be maintained. By using this novel and J.K. Rowling‟s equally famous book of wizarding tales, The Tales of Beedle the Bard, in which the wand makes an appearance, I will demonstrate that the moral we are being offered through both books is that the endless pursuit of power and the many promises of imagination are things that need to be controlled. As one of the characters of the famous saga, Professor Albus Dumbledore, once said in Harry Potter and the Philosopher’s Stone: “It does not do to dwell in dreams and forget to live.”